Cardamine occulta, the correct species name for invasive Asian plants previously classified as C. flexuosa, and its occurrence in Europe - Marhold, Karol (PhytoKeys, 2016)
Abstract. The nomenclature of Eastern Asian populations traditionally assigned to Cardamine flexuosa has remained unresolved since 2006, when they were found to be distinct from the European species Cardamine flexuosa. Apart from the informal designation “Asian Cardamine flexuosa”, this taxon has also been reported under the names Cardamine flexuosa subsp. debilis or Cardamine hamiltonii. Here we determine its correct species name to be Cardamine occulta and present a nomenclatural survey of all relevant species names. A lectotype and epitype for Cardamine occulta and a neotype for the illegitimate name Cardamine debilis (replaced by Cardamine flexuosa subsp. debilis and Cardamine hamiltonii) are designated here. Cardamine occulta is a polyploid weed that most likely originated in Eastern Asia, but it has also been introduced to other continents, including Europe. Here data is presented on the first records of this invasive species in European countries. The first known record for Europe was made in Spain in 1993, and since then its occurrence has been reported from a number of European countries and regions as growing in irrigated anthropogenic habitats, such as paddy fields or flower beds, and exceptionally also in natural communities such as lake shores.